Treaty Exit in the United States: Insights from the United Kingdom or South Africa? - Curtis A. Bradley; Laurence R. Helfer (AJIL Unbound, 2017)
Courts in the United Kingdom and South Africa have recently issued important rulings that have constrained the executive's authority to withdraw from treaties in those countries. This essay considers whether these rulings might offer insights for treaty exit issues in the United States. We first provide an overview of U.S. law and practice regarding the termination of international agreements. We next summarize the U.K. and South African decisions, which required parliamentary approval for pulling out of treaties establishing the European Union and the International Criminal Court (ICC), respectively. Finally, we consider the relevance of these rulings for treaty withdrawals in the United States. We conclude that they are unlikely to offer much guidance, both because of differences in the three countries' constitutions and because the reasoning of the U.K. and South African courts do not engage with the central arguments made in the United States concerning the President's unilateral authority to withdraw from treaties.